CONSTRUCTIVE FEATURES OF THE ASCERTAINING PART OF COMPARATIVE CONSTRUCTIONS (BASED ON WRITERS-DOCTORS’ LITERARY WORKS) - Valentina Mikhaylovna Mirzoeva; Anzhelika Alimovna Kuznetsova; Lyudmila Grigorevna Vitlinskaya; Mayya Il’inichna Volovich (Sovremennye Issledovaniâ Socialʹnyh Problem, 2019)
State of the problem. The article is aimed at studying the formal structure and structural features of the ascertaining part of single-component structures based on writers-doctors’ literary works. These syntactic units have not been described in detail so far and are considered, as a rule, in connection with constructions of a comparatively similar type, which leaves out the essential features of the syntactic units described in this article.